A preliminary investigation of the impact of oily skin on quality of life and concordance of self‐perceived skin oiliness and skin surface lipids (sebum). (21st June 2013) - Wu, Y.; Niu, Y.; Zhong, S.; Liu, H.; Zhen, Y.; Saint‐Leger, D.; Verschoore, M.
Synopsis Objective This preliminary study investigated both the impact of oily skin on quality of life (QoL) and the agreement between subjective oily skin self‐assessment and objective skin surface sebum measurement in young to middle‐aged Chinese women in Beijing. Methods A 18‐item Chinese version of the Oily Skin Self‐Image Questionnaire (OSSIQ) was used to assess the impact of oily skin on QoL in 300 healthy female subjects (age groups: 20–25; 26–30; 31–35, ). The subjects were divided equally into the oily skin group and the non‐oily skin group based on their self‐perception of skin oiliness. The level of skin surface lipids (SSL) was measured on the middle of the forehead, and both cheeks using the Sebumeter®. In order to assess the agreement between self‐perceived skin oiliness and measured SSL, we tentatively used the SSL median value as a dividing point to regroup all subjects. Results The results indicate that the Chinese version of the OSSIQ distinguished the oily skin group from the non‐oily skin group. Subjects in the oily skin group had significant higher emotional status score and behavior score when compared with subjects in the non‐oily skin group. Subjects in the oily skin group had higher SSL when compared with subjects in the non‐oily skin group, especially in younger age groups. The agreement between self‐perceived skin oiliness and measured SSL was moderately strong in younger age groups, and declined with age. Conclusion These results strongly suggest that having oily skin can cause a significant negative impact on QoL among Chinese women. The Chinese version of the OSSIQ is a reliable and valid tool for assessing the impact of oily skin on QoL. The accuracy of oily skin self‐assessment declines with age.